2020
DOI: 10.1016/j.jpainsymman.2020.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, Symptom Management, and Outcomes of 101 Patients With COVID-19 Referred for Hospital Palliative Care

Abstract: Hospital palliative care is an essential part of the COVID-19 response but data are lacking. We identified symptom burden, management, response to treatment, and outcomes for a case series of 101 inpatients with confirmed COVID-19 referred to hospital palliative care. Patients (64 men, median [interquartile range {IQR}] age 82 [72e89] years, Elixhauser Comorbidity Index 6 [2e10], Australian-modified Karnofsky Performance Status 20 [10e20]) were most frequently referred for end-of-life care or symptom control. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
189
4
44

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(258 citation statements)
references
References 10 publications
(11 reference statements)
11
189
4
44
Order By: Relevance
“…Among decedents and survivors with covid-19, breathlessness, cough, and fatigue are the most common symptoms 9. A case series of 101 patients with severe covid-19 who were referred to three hospital palliative care teams in London, UK, found breathlessness and agitation were the most common symptoms, alongside drowsiness and delirium 10…”
Section: Symptoms In Patients With Severe Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Among decedents and survivors with covid-19, breathlessness, cough, and fatigue are the most common symptoms 9. A case series of 101 patients with severe covid-19 who were referred to three hospital palliative care teams in London, UK, found breathlessness and agitation were the most common symptoms, alongside drowsiness and delirium 10…”
Section: Symptoms In Patients With Severe Covid-19mentioning
confidence: 99%
“…The use of continuous parenteral infusions can be useful to ensure a consistent background dose of opioid and enable titration according to symptom severity. An early case series of 101 hospitalised patients with covid-19 who were referred to palliative care found that opioids were usually effective for palliation of breathlessness, with a median dose of 10 mg (range 5-30 mg) subcutaneous morphine over 24 hours 10. A retrospective audit of 36 hospitalised patients with covid-19 who died outside critical care found that 26 of them had a subcutaneous infusion at the time of death, and the total mean opioid dose (subcutaneous morphine equivalent) during the final 24 hours was 16 mg 13…”
Section: How Can Breathlessness In Severe Covid-19 Be Managed?mentioning
confidence: 99%
“…It is now clear that COVID-19 itself is associated with painful symptoms, including myalgia, arthralgia, abdominal pain, headache, and chest pain, and even those not admitted to critical care environments may have pain requiring opioids for symptom management. 33 An important area to recognise is the psychological impact of COVID-19, with the unique social restrictions likely to create an additional burden. Severe psychological sequelae have been reported in ICU survivors with up to 30% of ARDS survivors developing post-traumatic stress disorder (PTSD).…”
mentioning
confidence: 99%
“…Eine Kohorte von 101 PatientInnen mit COVID-19-Infektion, die palliativmedizinisch betreut wurden, litt unter folgenden Symptomen [18]:…”
Section: Symptomkontrolleunclassified
“…10 Stunden)[19]. PatientInnen lagen mit 10-16 mg/24 h Morphinäquivalent und 10-13 mg/24 h Midazolam eher im unteren Dosisbereich[18,19]. Eine letztendliche Beurteilung, ob diese niedrigen Dosierungen insgesamt zur Symptomkontrolle ausreichen, kann aufgrund der wenigen Publikationen und singulären klinischen Erfahrungen derzeit nicht erfolgen.Angst und Unruhe PatientInnen mit Atemnot leiden häufig gleichzeitig unter Angst und Unruhe.…”
unclassified